Writing Perl Modules for CPAN - Tregar, Sam (Apress, 2013)
This book assumes you have a computer at your disposal with Perl installed. If not, then you can still read the book, but you won’t be able to try the examples. Many of the examples assume you’re working on a UNIX system, Perl’s “home court.” Where possible, I’ve noted differences under Microsoft Windows, but if you’re using anything more exotic, you may need to make minor adjustments to get the examples to work.